Solvolysis liquefaction and characterization of biopolyol prepared from liquefied oil palm fruit waste - Kormin, S.; M. Rus, A. Z.; M. Azahari, M. S. (African Journal Online (AJOL), 2018)
From our previous paper, the optimal liquefaction conditions for biopolyol production were determined to be PW/ PEG400 = 1/3, 5% (w/w) acid loading and liquefaction at 150°C for 120 min. Studies on their thermal properties were carried out by thermogrimetry analyzer (TGA). Chemical properties of each PW fibre and liquefied PW residue were investigated by X-ray diffraction analysis (XRD). The Fourier transform-infrared (FT-IR) were selected to analyze the functional group of PW fibre and liquefied PW residue. Liquefied PW residue had higher weight loss percent and lower residual ratios. In other word, the thermal stabilities of liquefaction residue decreased in TGA analysis. FT-IR of the PW fibre and liquefied PW biopolyol fraction confirmed the formation of larger amounts of long-chain lipophilic compounds under liquefaction conditions